Pengembangan Model Operasi Pompa Berkelanjutan di Daerah Irigasi Sumur Pompa Dangkal - Murtiningrum Murtiningrum; Sigit Supadmo Arif; Saiful Rochdyanto (agriTECH, 1996)
Model of sustainable pump operation in an unconfined groundwater irrigation system was developed to determine pump operation pattern which consist of the number of pumps, duration, and distance between pumps, so that crop water requirement is fulfilled and groundwater irrigation system is sustained. Total irrigation flow, EQpi, results in lowering water table which is called drawdown, sn. Drawdown sn should be less than di (sn< di) which (d1 is maximum drawdown which is affected by pump technology. Model outputs for the area of Sri Rahayu Farmer Group in Kedungtuban, Blora for existing cropping pattern show that average irrigation water requirement is 916.1mm/year and peak flow is 4.93 ips. It still can be fulfilled by 1, 2, 3, 4, or 9 pumps for 10 days operation continuously which is shown by the drawdowns which are less than maximum drawdown.